Ni2P‐Modified Ta3N5 and TaON for Photocatalytic Nitrate Reduction. Issue 8 (19th May 2020) - Wei, Lin; Adamson, Marquix A. S.; Vela, Javier
Abstract: Self‐sustaining photocatalytic NO3 − reduction systems could become ideal NO3 − removal methods. Developing an efficient, highly active photocatalyst is the key to the photocatalytic reduction of NO3 − . In this work, we present the synthesis of Ni2 P‐modified Ta3 N5 (Ni2 P/Ta3 N5 ), TaON (Ni2 P/TaON), and TiO2 (Ni2 P/TiO2 ). Starting with a 2 mM (28 g/mL NO3 − −N) aqueous solution of NO3 −, as made Ni2 P/Ta3 N5 and Ni2 P/TaON display as high as 79% and 61% NO3 − conversion under 419 nm light within 12 h, which correspond to reaction rates per gram of 196 μmol g −1  h −1 and 153 μmol g −1  h −1, respectively, and apparent quantum yields of 3–4%. Compared to 24% NO3 − conversion in Ni2 P/TiO2, Ni2 P/Ta3 N5 and Ni2 P/TaON exhibit higher activities due to the visible light active semiconductor (SC) substrates Ta3 N5 and TaON. We also discuss two possible electron migration pathways in Ni2 P/semiconductor heterostructures. Our experimental results suggest one dominant electron migration pathway in these materials, namely: Photo‐generated electrons migrate from the semiconductor to co‐catalyst Ni2 P, and upshift its Fermi level. The higher Fermi level provides greater driving force and allows NO3 − reduction to occur on the Ni2 P surface. Abstract : Photocatalytic reduction of NO3 − over visible‐light‐active Ni2 P‐modified Ta3 N5 or TaON photocatalysts is reported.